Comparative government and politics - Pushpa Singh,Ed; Chetna Sharma,Ed (Sage, 2019)
A wide-ranging, accessible and contemporary textbook capturing the narrative of comparative politics and its changing nature in the rapidly transforming world. comparative government and Politics introduces students to the tradition of comparative political research and explores the central ideas and questions that constitute the field. This textbook, written in close consultation with the syllabus and Course curriculums of major Indian universities, indulges in critical thematic exploration as well as detailed study of important political institutions and their functioning in comparative perspective. Instead of just summarizing European scholarly works with examples from the West, the book centralizes the experiences and case studies from postcolonial societies, making it relatable for the students of developing countries. It covers contemporary global debates pertinent to each topic and brings up important cases from the global South as well. Key features: discussions incorporate the intersectionality of gender, race and ethnicity Chapters begin with a reader guide feature to lay out the objective, structure and brief introduction of the br>Chapter Content content is aided by book-end glossary, list of Keywords and review questions for self-assessment.